Peranan Teknologi Informasi dalam Pengembangan E-Learning pada Fakultas Mipa di Indonesia - Polla, Gerardus (Bina Nusantara University, 2010)
The fast development of information technology has changed paradigm of human life in almost all aspects and their activities, including education. This paper is purposed to discuss about IT ability and its function in supporting all education events and activities. One of education need development alternatives in science and mathematics (MIPA) faculty in Indonesia is the needs of IT development that could support long distance educational system in a virtual university form. This paper also describes about how IT support educational theories like constructivist, colaborative learning that has been transformed in learning method from teacher-centered into student-centered in creating student culture of self-learning in MIPA faculty.